Enhancing Methodological Reporting in Public Administration: The Functional Equivalents Framework. Issue 8 (November 2020) - Mele, Valentina; Esteve, Marc; Lee, Seulki; Bel, Germà; Cappellaro, Giulia; Petrovsky, Nicolai; Ospina, Sonia M.
Public administration scholarship reflects a multidisciplinary field in which many theoretical perspectives coexist. However, one of the dark sides of such theoretical pluralism is methodological fragmentation. It may be hard to assess the research quality and to engage with the findings from studies employing different methodologies, thus limiting meaningful conversations. Moreover, the constant race across social sciences to make methodologies more sophisticated may exacerbate the separation between academic and practitioner audiences. To counterbalance these two trends, this article aims at increasing methodological intelligibility in our field. It does so starting from the idea that each methodology entails choices in the conventional phases of research design, data collection, and data analysis, and that these choices must be reported. The paper nails down and exemplifies such reporting needs for five selected methodologies: survey studies, quantitative experimental studies, quantitative observational studies, qualitative case studies and ethnographies. Based on their discussion and comparison, the paper offers a framework composed by functional equivalents, that is to say, the common denominator among methodological reporting needs. Methodological choices that need reporting include the rationale for the selection of a methodology, delimitation of the study, the research instrument, data processing and ethical clearance. Increasing methodological reporting would facilitate dialogues among different methodological communities, and with practitioner readers. All of which would also promote field building in the scholarship of public administration.